2018
DOI: 10.4274/mirt.51423
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of 18F-FDG PET/CT to Staging of Head and Neck Malignancies

Abstract: Objective:Accurate staging of head and neck cancer (HNC) plays an important role in patient management as well as protection of functional characteristics of the head and neck region. Our aim was to investigate the contribution of 2-[18F]-fluoro-2-deoxy-d-glucose (FDG) positron emission tomography/computed tomography (PET/CT) as part of HNC staging to clinical evaluation and treatment planning.Methods:Clinical records of 138 HNC cases who has undergone 18F-FDG PET/CT imaging were retrospectively reviewed. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…We obtained the pooled OR value of 3.088 with 95% CI of [1.486; 6.419]. Data used for this analysis were heterogeneous, and we achieved the Q value of 33.8%, df value of 13, I 2 value of 61.5% (31.23-78.5), 2011 10 Pereira et al 2012 11 Karapolat and Kumanlıoğlu 2012 12 Gődény et al 2016 13 Ceylan et al 2018 14 Sherif et al 2018 15 Schroeder et al…”
Section: Meta-analysis Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…We obtained the pooled OR value of 3.088 with 95% CI of [1.486; 6.419]. Data used for this analysis were heterogeneous, and we achieved the Q value of 33.8%, df value of 13, I 2 value of 61.5% (31.23-78.5), 2011 10 Pereira et al 2012 11 Karapolat and Kumanlıoğlu 2012 12 Gődény et al 2016 13 Ceylan et al 2018 14 Sherif et al 2018 15 Schroeder et al…”
Section: Meta-analysis Resultsmentioning
confidence: 96%
“…However, because of the high sensitivity and specificity of 18 F-FDG PET for cellular change and tumors, its use is highly recommended in various studies due to its high sensitivity in detecting perineural spread and recurrent metastatic tumors. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] For example, Linz et al reported the sensitivity of 18 F-FDG PET as 78.6% and specificity as 83.1%. 19 Similarly, Sherif et al reported a high sensitivity of 83.33% and specificity of 89.47%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 5 ] reported an average 3.4 mm underestimation of the extent of SCC invasion into the mandible when using radiological imaging. For head and neck cancer detection, reported sensitivity values for positron emission tomography/computed tomography (CT) scans range from 0.68% [ 6 ], for CT scans—85.7% [ 7 ] and magnetic resonance imaging scans—75.8% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%